Suppression of capsule expression in Δlon strains of Escherichia coli by two novel rpoB mutations in concert with HNS: possible role for DNA bending at rcsA promoter. Issue 5 (25th September 2015) - Meenakshi, Shanmugaraja; Munavar, M. Hussain
Abstract Analyses of mutations in genes coding for subunits of RNA polymerase always throw more light on the intricate events that regulate the expression of gene(s). Lon protease of Escherichia coli is implicated in the turnover of RcsA (positive regulator of genes involved in capsular polysaccharide synthesis) and SulA (cell division inhibitor induced upon DNA damage). Failure to degrade RcsA and SulA makes lon mutant cells to overproduce capsular polysaccharides and to become sensitive to DNA damaging agents. Earlier reports on suppressors for these characteristic lon phenotypes related the role of cochaperon DnaJ and tmRNA. Here, we report the isolation and characterization of two novel mutations in rpoB gene capable of modulating the expression of cps genes in Δlon strains of E. coli in concert with HNS. clpA, clpB, clpY, and clpQ mutations do not affect this capsule expression suppressor (Ces) phenotype. These mutant RNA polymerases affect rcsA transcription, but per se are not defective either at rcsA or at cps promoters. The results combined with bioinformatics analyses indicate that the weaker interaction between the enzyme and DNA::RNA hybrid during transcription might play a vital role in the lower level expression of rcsA. These results might have relevance to pathogenesis in related bacteria.